Karnataka Draft Sixth Five Year Plan 1980-85 Volume-I Strategy, Outlays and Programmes - Planning Commission (Planning Commission, 1980)
An assessment of the development performance vis-a-vis the development outlay is necessary for evolving an approach to medium and long-term Plans. Hence, a brief review of the development outlay and performance is presented here covering the period 1969-70 to 1979-80. This period covers the Fourth Plan period, four years of the Fifth Five Year Plan period and two Annual Plan periods of the Medium Term Plan, namely, 1978-79 and 1979-80. 1979-80 is the base year of the new Sixth Plan.
Karnataka, Planning Department